Prolonged efficacy of the 300IR 5-grass pollen tablet up to 2 years after treatment cessation, as measured by a recommended daily combined score - Didier, Alain (Clin Transl Allergy, 2015)
BACKGROUND: The 300IR (index of reactivity) 5-grass pollen tablet has favorable short-term and sustained clinical efficacy in patients with grass pollen-induced allergic rhinoconjunctivitis (ARC). Here, we report maintenance of efficacy and safety over 2 years following treatment discontinuation. METHODS: Randomized, double-blind, placebo-controlled, parallel-group, multicenter Phase 3 trial in patients aged 18–50 years with ARC. During study years 1–3, patients received a daily sublingual tablet containing either 300IR 5-grass pollen extract or placebo, according to a discontinuous pre- and coseasonal protocol. Study years 4 and 5 were treatment-free. In response to health authorities’ recommendations, the daily combined score (DCS) was assessed in a post-hoc analysis as the efficacy endpoint. Components of the DCS were daily rhinoconjunctivitis total symptom score (DRTSS) and daily rescue medication score (DRMS). RESULTS: 633 patients with ARC were randomized to placebo (n = 219) or 300IR 5-grass pollen tablet, beginning 4 months (4 M, n = 207) or 2 months (2 M, n = 207) prior to the estimated start of the grass pollen season and continuing until season’s end. During the first post-treatment year, a statistically significant difference versus placebo in least squares (LS) mean DCS was noted in patients previously receiving active treatment (300IR (2 M) point estimate: −0.16, 95% confidence interval (CI(95%)): [−0.26, −0.06], p = 0.0019; −31.1%; 300IR (4 M) point estimate: −0.13, CI(95%): [−0.23, −0.03], p = 0.0103, −25.3%). During the second post-treatment year, patients in the 300IR (4 M) group, but not the 300IR (2 M) group, showed a statistically significant difference in LS mean DCS versus placebo (point estimate: −0.11, CI(95%): [−0.21; 0.00], p = 0.0478, −28.1%). This significant efficacy seen during the post-treatment years in patients previously treated with 5-grass pollen tablet compared favorably with that during the 3 prior years of active treatment. A statistically significant difference versus placebo was also noted in secondary efficacy measures in both post-treatment years (except for DRTSS in year 5). In the absence of any active treatment, the safety profile was similar in the active groups versus placebo group during either post-treatment year. CONCLUSIONS: In adults with grass pollen-associated ARC, 5-grass pollen tablet therapy beginning 4 months before the pollen season and continuing to season’s end demonstrated efficacy across all variables during active treatment, and this effect was prolonged for up to 2 years post-treatment. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT00418379.